Medardo Angel Silva: Unuterrable voices and being cholo in Guayaquil - Benavides, Hugo (2007)
The article looks to assess the particular power that Silva’s sensibility came to have over his city of origin, exploring what are some of the major sentiments or tropes that enabled Silva’s paradigmatic place in the city’s understanding of itself and its way of being? What are some of the major effects of sentiments that catapulted themselves again and again to the city’s multiple generations? The article also explores how these same effects of sentiments would contribute to Silva’s high regard in the official culture, and evidences the fact that Silva’s iconic figure has continuously and historically reflected the city’s own ambivalence over its own questions of origins and identity. Finally, the article poses that in Silva, fleeing streams of Guayaquilean generations have had a mirror with myriad levels of realities upon which to reflect their own bitter truths of un-belonging, colonial nightmares, and rejecting consequences of civilizing manners and norms.